2021
DOI: 10.3390/nano11061578
|View full text |Cite
|
Sign up to set email alerts
|

Sustained In-Vivo Release of Triptorelin Acetate from a Biodegradable Silica Depot: Comparison to Pamorelin® LA

Abstract: Triptorelin acetate was encapsulated into silica microparticles by spray-drying a mixture of colloidal silica sol and triptorelin acetate solution. The resulting microparticles were then combined with another silica sol containing silica nanoparticles, which together formed an injectable silica-triptorelin acetate depot. The particle size and surface morphology of the silica-triptorelin acetate microparticles were characterized together with the in vitro release of triptorelin, injectability and rheology of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Table 6 provides a summary of chromatographic and electrophoretic methods used for determination of triptorelin in biological samples, i.e., plasma, serum, and urine. Determination of triptorelin has been typically performed with the use of liquid chromatography (LC) coupled with MS [25,[42][43][44][45][46][47] or UV detection [48,49]. Actually, the only CE method developed for biological samples is this one presented in our work.…”
Section: Comparison Of Methods For Triptorelin Analysis In Biological Samplesmentioning
confidence: 99%
“…Table 6 provides a summary of chromatographic and electrophoretic methods used for determination of triptorelin in biological samples, i.e., plasma, serum, and urine. Determination of triptorelin has been typically performed with the use of liquid chromatography (LC) coupled with MS [25,[42][43][44][45][46][47] or UV detection [48,49]. Actually, the only CE method developed for biological samples is this one presented in our work.…”
Section: Comparison Of Methods For Triptorelin Analysis In Biological Samplesmentioning
confidence: 99%
“…Silica microparticles encapsulating triptorelin acetate formed an injectable depot with sustained release characteristics, exhibiting pharmacodynamic effects comparable to those of commercially available products [83]. The controlled release of bone morphogenetic protein-2 (BMP-2) from a three-dimensional tissue-engineered nano-scaffold resulted in significant ectopic bone formation, further underscoring its potential for tissue regeneration [84].…”
Section: Drug Deliverymentioning
confidence: 99%
“…The biodegradation process does not change the pH within silica gel or in the surrounding tissue, in contrast to other commonly used polymeric LAI technologies. Further, it has been shown that the silica matrix is chemically and physically compatible with small molecules, monoclonal antibodies, peptides, and proteins. …”
Section: Introductionmentioning
confidence: 99%